Campus Grid Computing System - Qdemat, Ibrahim; Dwaib, Muhammad (جامعة بولتكنك فلسطين - هندسة الحاسوب, 2014)
Grid computing is a service for sharing computer power and data storage capacity over the Internet. This project aims to increase the utilization of the available computing resources in PPU. Computing resources at different facilities of the university especially those in labs are almost idle for long periods of time or for scattered periods. These resources can be exploited in another place or for other computational tasks in the university. The goal of this project is to develop a grid computing system that provides the research units with a large computational power to enable the working on a computational-intensive experiments that may not be able to handle previously. In addition, this project aims to operate a grid computing system with minimal costs. Hardware costs are eliminated since the project will use the hardware components that are already exist in the university, no additional components are needed. Software costs approaches to zero since all the dedicated software needed to develop the system are free open source software. So we will get a system that will provide a large computing power with a minimal cost. الملخص: الحوسبة الشبكية هي احد مجالات الانظمة الموزعة والتي تهدف الى استغلال القدرة الحسابية للأجهزة الموزعة على الشبكة لتشكيل حاسوب ظاهري بقدرة معالجة فائقة. يتم ذلك عن طريق تقسيم المشاريع الضخمة الى اجزاء مستقلة بحيث يتم توزيع هذه الاجزاء على الاجهزة التي تكون في حالة الخمول والتي تعمل بدورها على معالجة هذه الاجزاء وتعيد النتائج. هناك العديد من المرافق في الجامعة التي تحتاج الى قدرات حسابية هائلة لكي تتمكن من انجاز مهامها بالشكل الصحيح بالإضافة إلى العديد من الأبحاث التي تحتاج إلى وقت طويل إذا تم تنفيذها على أجهزة حاسوب عادية. ويمكن توفير هذه القدرات الحسابية العالية عن طريق تزويد هذه المرافق بالحواسيب ذات القدرات الهائلة (super computers). ولكن هذه الحواسيب ذات كلفة باهظة وفي اغلب الاحيان ليست متوفرة لنا في فلسطين. وفي المقابل يمكن ايضا توفير القدرات الحسابية الهائلة عن طريق بناء نظام الحوسبة الشبكية الذي يعمل على تجميع القدرات الحسابية لأجهزة الحاسوب الموجودة في مختبرات الحاسوب المختلفة بحيث نحصل على جهاز حاسوب ظاهري فائق القدرة يمكنه تزويد المرافق المختلفة بالقدرات الحسابية التي تحتاج اليها. اثناء هذا المشروع سنعمل على اجراء دراسة عملية لحساب نسبة استغلال القدرة الحسابية للأجهزة الموجودة في مختبرات الجامعة. ايضا سنعمل على بناء نظام الحوسبة الشبكية على مجموعة من الاجهزة . وفي النهاية سنقوم بتزويد النظام بالقدرة على استقبال وظائف حسابية من المستخدمين ليقوم بمعالجتها وارجاع النتائج.
Keywords: Campus Grid Computing System